2020
DOI: 10.1002/cam4.3543
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of FREM1 in breast cancer indicates favorable prognosis and high‐level immune infiltration status

Abstract: Zhi-fang Yang 1 This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
(89 reference statements)
1
22
0
Order By: Relevance
“…In particular, knockout of FRAS1 inhibits proliferation of gastric cancer cells through caspase activity increment and cell cycle arrest both in vitro and in vivo [49]. Conversely, increased expression of FREM1 in breast cancer is associated with a favorable prognosis and high-level immune infiltration status [50].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, knockout of FRAS1 inhibits proliferation of gastric cancer cells through caspase activity increment and cell cycle arrest both in vitro and in vivo [49]. Conversely, increased expression of FREM1 in breast cancer is associated with a favorable prognosis and high-level immune infiltration status [50].…”
Section: Discussionmentioning
confidence: 99%
“… 8 FREM1, in contrast, has been identified as an essential component for embryonic development and involves immune cell migration. 6 , 9 FREM1 gene (encoding 2179 amino acids) has ~15 splice variants, 10 , 11 including TILRR (encoding 715 amino acids). 6 As a shorter isoform of FREM1, the transcriptional start site of TILRR is present in an intronic segment between exons 24 to 25 of the FREM1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Because FREM1 is an extracellular matrix protein and widely expressed in the regions of epithelial-mesenchymal interaction [3], its expression in epithelial tissues may promote immune cell infiltration. Using immunohistochemistry (IHC) and immunofluorescence (IF) assays, a study demonstrated that elevated expression of FREM1 in normal breast/mammary epithelial tissues is positively correlated with the in-filtration of several immune cells, such as CD4+, and CD8+T -cells, and M1 (inflammatory) macrophages [47]. In addition, analysis of breast cancer (BC) epithelial tissues showed that high FREM1-expressed BC tissues harbor abundant CD4+T memory cells (resting and activated), CD8+T-cells, M1 macrophages, resting dendritic cells, gamma-delta T cells (γδT), B-cells (naive and memory), plasma cells, and resting mast cells.…”
Section: Frem1 and Immune Cell Infiltrationmentioning
confidence: 99%
“…In addition, analysis of breast cancer (BC) epithelial tissues showed that high FREM1-expressed BC tissues harbor abundant CD4+T memory cells (resting and activated), CD8+T-cells, M1 macrophages, resting dendritic cells, gamma-delta T cells (γδT), B-cells (naive and memory), plasma cells, and resting mast cells. Contrastingly, low FREM1-expressed BC tissues tended to have a higher proportion of M2 (anti-inflammatory) macrophages, neutrophils, and resting NK (natural killer) cells [47]. It has also been shown that the RGD motif of ECM binds with integrins and promotes migration of effector T cells into the interstitial inflamed tissues [48].…”
Section: Frem1 and Immune Cell Infiltrationmentioning
confidence: 99%
See 1 more Smart Citation